Non-useful Papanicolaou smears. Analysis of their causes in the first semester 2005 in Cienfuegos city, Cuba - Miryam Magalys González González del Pino; Teresita Sabatés Llerandi; Mayrim Hernández González (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Background: Cervicouterine cancer is a common type of cancer in women. It is one of the three main death causes in women after breast and colon cancer. It is the first cause of mortality among malignant neoplasias in the female reproductive apparatus. Objective: to determine the causes of non-useful Papanicolaou smear in Cienfuegos' province. Method: a retrospective study which had the non-useful Papanicolaou smear of the 1st semester of the year 2005 as samples the following variable were analyzed; age, health area and cause. Results: the main cause was the absence of the endocervical cells in the samples (91,1 %). The most affected health area were Palmira (8,83 %), Health area III (8,08 %) and Juraguá (7,14 %). The higher quantity of non-useful Papanicolaou smear was found in the 30-39 year-old group. Conclusions: Although, the majority of health areas have an index below the 5% of non-useful Papanicolaou smear, there are still difficulties to fulfill adequately the program of early detection of Cervicouterine cancer, due to the issues faced when taking the samples.